Analysis of the Implementation of the Occupational Safety and Health (K3) System and the Implementation of Risk Management in the Cipunten Agung Hilir River Flood Handling Construction Project, Labuan District - Maddeppungeng, Andi; Asyiah, Siti; Setiawati, Dwi Novi; Ujianto, Rifky; Priyatno, Yusup (Jurnal Fondasi, 2023)
Construction projects require working time specifications that need to be completed in a short time. But in practice, some interfere with the implementation. This study aims to determine whether the OHS system has been implemented in construction projects. The applications of risk management in construction projects. This study was conducted as part of the Shipunten Agung Hill River Flood Management Project in the Labuan District. The method used is the distribution of questions to be filled out by respondents who are involved in projects in the OHS Section. The type of research in this research is quantitative. Quantitative research is research that distributes surveys in the form of questionnaires to respondents and the data is processed to determine the correlation between the results of the data obtained. Processing data in this study using SPSS v.20 software to test simple linear regression analysis. The results showed that the K3 system had been applied to the project by 64.8%. The most dominant variable affecting the implementation of the OHS system and the application of risk management in construction projects is that signs/signs/information about the project have been installed around the project site with a coefficient value of 6,053 and the variable that has the lowest effect on the application of the OHS system and the application of risk management to the project.